(untitled) (Ibrahim Medical College Journal, 2009)
Health Performance Indicators are often utilized as tools for assessing and evaluating the success of different national health programs in achieving their desired outcomes in the health sector. This review article aims to show the trends in health improvement in Bangladesh. The indicators selected are Life expectancy at Birth, Crude Birth and Death Rates, Infant Mortality Rate, Maternal Mortality Ratio and Prevalence of Low Birth Weight. Life Expectancy at Birth shows an increasing trend for both sexes; where as all the four mortality indicators show a declining trend. The trend in Low Birth Weight Prevalence suggests that the desired decline in this field has not yet been achieved and continues as a public health problem. The overall picture suggests that Bangladesh has gone far to achieve the targets of MDG although a lot of formidable challenges are yet to be met. Ibrahim Med. Coll. J. 2007; 1(2): 21-24 Key Words: Performance indicators, health attainment. doi: 10.3329/imcj.v1i2.2905